Genomic Analysis of the Endophytic Stenotrophomonas Strain 169 Reveals Features Related to Plant-Growth Promotion and Stress Tolerance - Ulrich, Kristina; Kube, Michael; Becker, Regina; Schneck, Volker; Ulrich, Andreas (Frontiers in Microbiology, 2021)
Plant-associated Stenotrophomonas isolates have great potential for plant growth promotion, especially under stress conditions, due to their ability to promote tolerance to abiotic stresses such as salinity or drought. The endophytic strain Stenotrophomonas sp. 169, isolated from a field-grown poplar, increased the growth of inoculated in vitro plants, with a particular effect on root development, and was able to stimulate the rooting of poplar cuttings in the greenhouse. The strain produced high amounts of the plant growth-stimulating hormone auxin under in vitro conditions. The comparison of the 16S rRNA gene sequences and the phylogenetic analysis of the core genomes showed a close relationship to Stenotrophomonas chelatiphaga and a clear separation from Stenotrophomonas maltophilia. Whole genome sequence analysis revealed functional genes potentially associated with attachment and plant colonization, growth promotion and stress protection. In detail, an extensive set of genes for twitching motility, chemotaxis, flagella biosynthesis and the ability to form biofilms, which are connected with host plant colonization, could be identified in the genome of strain 169. The production of indole-3-acetic acid and the presence of genes for auxin biosynthesis pathways and the spermidine pathway could explain the ability to promote plant growth. Furthermore, the genome contained genes encoding for features related to the production of different osmoprotective molecules and enzymes mediating the regulation of stress tolerance and the ability of bacteria to quickly adapt to changing environments. Overall, the results of physiological tests and genome analysis demonstrated the capability of endophytic strain 169 to promote plant growth. In contrast to related species, strain 169 can be considered nonpathogenic and suitable for biotechnology applications.